Nivolumab Effective for Gastric and Lung Cancers but Not for Multiple Myeloma in a Multiple Primary Cancer Patient - Tsukasa Yasuda; Junji Hiraga; Michihiko Narita; Yoshimasa Tanikawa; Tomoyuki Tsuzuki (Case Reports in Hematology)
The case of a 76-year-old man with multiple primary cancers that were treated with nivolumab is presented. Six years earlier, he was diagnosed with multiple myeloma (MM) and was treated with several chemotherapies. He was also diagnosed with gastric cancer with liver metastasis and primary lung cancer by upper gastrointestinal endoscopy and computed tomography (CT). Nivolumab treatment was given as third-line therapy, and it was effective for gastric and lung cancers. But MM worsened, and the patient died. There is no standard treatment for multiple primary cancers, and the development of effective treatments for multiple primary cancers is important.